Classification of Locative Prepositions in Toba Batak Language - Juni Agus Simaremare; Mahriyuni; Dwi Widayati; Erikson Saragih (proceedings.icesy, 2026)
This research is based on the differences in the classification of locative prepositions in various languages. The purpose of this research is to describe the classification of locative prepositions in the Toba Batak language in locative constructions. This type of research is qualitative research. The results of this study found that the Toba Batak language has seven simplex locative prepositions, namely di ’in’, tu ’to’, sian ’from’, di ’on’, sahat ’until’, rodi ’until’, salpu/bolus ’through’. These seven prepositions can be classified into two, namely true simplex prepositions and simplex prepositions resulting from the grammaticalization process. The true locative prepositions are di ’in’, tu ’to’, sian ’from’. Meanwhile, the simple prepositions resulting from the grammaticalization process are di ’on’, sahat ’until’, rodi ’until’, salpu/bolus ’pass’. Meanwhile, complex prepositions can be divided into two subgroups, namely (1) Affixed complex prepositions, namely prepositions with the affixes mang- and mang-i and (2) compound complex prepositions consisting of adjacent and correlated prepositions.